The Role of Neutrophil-Lymphocyte Ratio (NLR), Platelet-Lymphocyte Ratio (PLR), and D-Dimer in Predicting the Outcome of Confirmed COVID-19 patients - Fathiyah Isbaniah; Tomu Juliani; Triya Damayanti; Dewi Yenita; Faisal Yunus; Budhi Antariksa; Wahyu Aniwidyaningsih; Sita Laksmi Andarini; Diah Handayani (Jurnal Respirologi Indonesia, 2021)
Background: Cytokine storm or hyperinflammation condition in COVID-19 patients could result in fatal outcomes. Inflammation could also result in coagulation disorders. The Neutrophil-Lymphocyte Ratio (NLR) and Platelet-lymphocyte ratio (PLR) have been known as inflammation markers in several diseases. D-dimer value can be used to assess a patient's coagulation status. Further study on thromboinflammation biomarkers in COVID-19 patients is needed. Therefore, we conducted a study to assess the association between NLR, PLR, and d-dimer on the clinical outcome of confirmed COVID-19 patients at Persahabatan Central Hospital.Methods: Observational cohort retrospective analysis was conducted on 214 medical records of confirmed COVID-19 patients who meet the inclusion criteria in Persahabatan Central Hospital from March to July 2020.Results: The mean patient’s age in this study is 54.35 years, dominated by male patients (60.7%). Most of the patients had normal nutritional status (54.7%). The proportion of patients with comorbidities is 65.4%. The most common comorbid is hypertension, followed by diabetes mellitus. 76.1% of patients have severe-critically ill disease, followed by moderate (20.1%) and mild disease (3.7%) The length of hospitalization median were 12 days. Sixty patients (28%) have died during hospitalization. The median of initial value of NLR, PLR, and d-dimer is 5.75 (0.68–81.5), 243.5 (44.7–1607), and 1140 (190–141300) respectively. We found significant associations between NLR (p = 0.000), PLR (p=0.013) and d-dimer (p = 0.032) on clinical outcome. Conclusion: Initial value of NLR, PLR, and D-dimer of confirmed COVID-19 patients at Persahabatan Central Hospital were associated with clinical outcome.